Bone Mineral Density and Serum Biochemical Predictors of Bone Loss in Patients with CKD on Dialysis - Malluche, Hartmut H. (American Society of Nephrology, 2014)
BACKGROUND: and objectives Use of bone mineral density (BMD) by dual-energy x-ray absorptiometry (DXA) is controversial for diagnosing bone loss in CKD patients on dialysis. The alternative quantitative computed tomography (QCT) is expensive and requires high radiation exposure. This study compared the two techniques and evaluated serum biochemical parameters for prediction of bone loss. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This prospective study enrolled patients from dialysis centers throughout Kentucky. BMD of the spine and hip was measured at baseline and after 1 year by DXA and QCT. Customary and novel serum biochemical parameters were obtained at the same times, including calcium, phosphorus, whole and intact parathyroid hormone, bone-specific alkaline phosphatase, procollagen type 1 N-terminal propeptide, tartrate-resistant acid phosphatase-5b, Dickkopf-1, fibroblast growth factor, and sclerostin. Rates of detection of osteoporosis by DXA and QCT were compared. Correlations were calculated between baseline biochemical parameters and BMD at baseline and changes over 1 year. Multivariable regression was performed to adjust for age, sex, body mass index, and race. RESULTS: Eighty-one patients completed the study (mean age=52.6±12.3 years, 56% men, 53% African American, and median dialysis vintage=41 months). At baseline, QCT and DXA of the spine identified similar rates of osteoporosis (13.6% and 13.6%), but at the hip, DXA identified more osteoporosis (22.2% versus 13.6%). At any site and by either method, 33.3% of the patients were osteoporotic. Baseline BMD correlated with sclerostin, intact parathyroid hormone, bone-specific alkaline phosphatase, tartrate-resistant acid phosphatase-5b, and fibroblast growth factor. At 1 year, hip QCT identified a higher number of patients experiencing bone loss (51.3%) than DXA (38.5%). After multivariable adjustment, baseline sclerostin and tartrate-resistant acid phosphatase-5b predicted bone loss measured by QCT of the hip; procollagen type 1 N-terminal propeptide predicted cortical spine bone gain by QCT. CONCLUSIONS: QCT identified prospectively more bone loss at the hip than DXA. The baseline serum biochemical parameters sclerostin and tartrate-resistant acid phosphatase-5b were noninvasive independent predictors of bone loss in CKD patients on dialysis.